Characterization of probiotic Bacillus sp. NP5 metabolites and their effect on female catfish broodstock re-maturation - Valensia Enzeline; Widanarni Widanarni; Agus Oman Sudrajat; Alimudin Alimudin (Jurnal Akuakultur Indonesia)
Probiotics are believed to contain active components that influence fish reproduction. This study aimed to evaluate the metabolite compounds present in the probiotic Bacillus sp. NP5 and their effect on female catfish broodstock re-maturation. The first step involved analyzing the metabolite content of the probiotic using liquid chromatography with tandem mass spectrometry (LCMS/MS). Subsequently, feed supplementation with the probiotic was implemented at concentrations of 106 CFU/g (P6), 108 CFU/g (P8), and control (C). Parameters observed included the metabolite content of Bacillus sp. NP5, gonadosomatic index (GSI), hepatosomatic index (HSI), gonad histology, gonad maturity rate, fecundity, number of matured eggs, distribution of egg diameter, fertilization rate (FR), hatching rate (HR), larval survival rate (SR), re-maturation period, and percentage of matured broodstock. The results showed that metabolites such as resveratrol (22.45%) and indoline (7.11%) are likely to influence the fish reproduction directly. Other metabolites, such as oxyresveratrol (22.95%) and vestitol (4.14%), are also thought to play an indirect role in reproduction. The supplementation demonstrated the best reproductive performance at 108 CFU/g treatment, with an increased GSI (14.74%), HSI (1.65%), gonad maturity rate, percentage of mature eggs (86.00%), re-maturation period (4 weeks), percentage of matured broodstock (100%), fecundity (243,605 eggs/broodstock), FR (98.74%), HR (80.62%), and SR (87.31%). The application of probiotic Bacillus sp. NP5 can accelerate re-maturation and enhance reproductive performance of female catfish broodstock. Probiotics contain metabolites that positively affect reproduction and can serve as an alternative to improve reproductive performance in female catfish broodstock.